2022
DOI: 10.1097/prs.0000000000009528
|View full text |Cite
|
Sign up to set email alerts
|

Defining Spatial and Temporal Resolution of Edema Following Rhinoplasty: A Three-Dimensional Topographical Analysis

Abstract: The published (albeit limited) experience with breast implant capsule-associated squamous cell carcinoma suggests that this is a much more aggressive pathology than BIA-ALCL, with more aggressive surgical management, as well as adjuvant therapy, necessary for disease management. 3,4,6 Our patient had transaxillary, periareolar, and inframammary incisions used in her previous augmentation and subsequent revisions, putting her at risk for ductal transection, implant colonization with biofilmproducing organisms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…This has an important clinical implication, as swelling in the nasal tip may be more noticeable due to the complexity of the surface anatomy. 5 This underscores the positive effect of 3D-printed splints compared with nasal taping on nasal tip postoperative edema, as the taping group did not demonstrate significant volume reduction after the 6 week time point.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…This has an important clinical implication, as swelling in the nasal tip may be more noticeable due to the complexity of the surface anatomy. 5 This underscores the positive effect of 3D-printed splints compared with nasal taping on nasal tip postoperative edema, as the taping group did not demonstrate significant volume reduction after the 6 week time point.…”
Section: Discussionmentioning
confidence: 62%
“…4 Previously our group reported on postoperative edema resolution, and its effect on the nasal contour, and demonstrated the total amount of postoperative edema to be relatively greater in the dorsum versus the nasal tip. 5 Additionally, our prior study revealed that although dorsal edema is greater than that of the nasal tip, the dorsal volume exhibited faster resolution of edema. The results of this study support this notion by demonstrating postoperative edema resolving more quickly in the dorsum when compared with the nasal tip in the 3D-printed splint group.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations